Identification of Biomphalaria havanensis and Biomphalaria obstructa populations from Cuba using polymerase chain reaction and restriction fragment length polymorphism of the ribosomal RNA intergenic spacer - Teofânia HDA Vidigal; Roberta L Caldeira; Andrew JG Simpson; Omar S Carvalho (Memorias do Instituto Oswaldo Cruz, 2001)
In Cuba, several Biomphalaria species have been reported such as B. orbignyi, B. schrammi, B. helophila, B. havanensis and B. peregrina; only the latter three are considered as potential hosts of Schistosoma mansoni. The specific identification of Biomphalaria species is based on anatomical and morphological characters of genital organs and shells. The correct identification of these snails is complicated by the high variation in these characters, similarity among species and in some cases by the small size of the snails. In this paper, we reported the classical morphological identification, the use of PCR and RFLP analysis of the internal transcribed spacer region of the ribosomal RNA genes for molecular identification of seven snail populations from different localities in Cuba. Using morphological and molecular analysis, we showed that among the studied Cuban Biomphalaria populations only B. havanensis and B. obstructa species were found.